A case study of professional role transition for occupational therapists in specialised education in post-apartheid South Africa : a critical narrative perspective - Sonday, Amshuda (Department of Health and Rehabilitation Sciences, 2016)
Background: This study is a critical description and explanation of the situated nature of the professional role transition process experienced by occupational therapists working in specialised education in post-apartheid South Africa. The study posed the research question: How do occupational therapists experience the process of professional role transition within specialised education in the Western Cape? The study was framed conceptually within critical social theory and occupational science. Aim: The study aimed to describe and analyse a single instrumental case of professional role transition experienced by five occupational therapists currently working at special school resource centres in two education districts in the Western Cape, South Africa Objectives: The objectives of the study were to: Describe and explain the process of professional role transition as experienced by occupational therapists along a trajectory from 1994 to 2013; Provide insights into the occupational therapists' perceptions, thoughts, feelings and attitudes on their professional role transition experience; Determine whether there are any role changes present and the possible impact this might have on the role and scope and development of occupational therapy practice within specialised education; and Outline the influences the socio political context has on the role of occupational therapists working in special school resource centres in the Western Cape.